New records of water mites of the genus Atractides Koch, 1837 (Acari: Hydrachnidia, Hygrobatidae) from Thailand, Malaysia and Sulawesi (Indonesia), with the description of four new species - Pesic, Vladimir; Smit, Harry (Zootaxa, 2009)
New records of water mites of the genus Atractides Koch, 1837 (Acari: Hydrachnidia, Hygrobatidae) from Thailand, Malaysia and Sulawesi are presented. Four species new to science, Atractides siamis, A. malayensis, A. tahanensis and A. sulawesiensis, are described; a first description of the male is given for Atractides putihi Wiles, 1991; a first description of the female is given for Atractides tenuipalpis Lundblad, 1969 and A. incertus Lundblad, 1969; two subspecies are elevated to species rank (with their former stem species in parentheses): A. substriatus Lundblad, 1969 (incertus), A. cognatus (K. Viets, 1935) (spatiosus); first records are given for Atractides incertus Lundblad, 1969 (Thailand), A. schwoerbeli Lundblad, 1969 (Thailand, Malaysia), A. tenuipalpis Lundblad, 1969 (Thailand), A. cognatus (K. Viets, 1935) (Thailand) and A. putihi Wiles, 1991 (Thailand).